2017
DOI: 10.2174/1381612823666170503150313
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and Sperm Quality in the Aging Male

Abstract: Parenthood at an older age is becoming a trend among men, especially in the most developed societies. Aging has a significant impact on male fertility. Older men exhibit notable disturbances in the reproductive axis, with steroidogenesis being impacted much more than spermatogenesis. The endocrine changes, together with morphological and functional alternations of the aging testis, result in decreased testosterone production. Nonetheless, studies are needed to scrutinize the impact of age per se versus age-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 0 publications
3
60
1
2
Order By: Relevance
“…sex hormones levels (Haji et al, 1994;Petersen et al, 2015;Li et al, 2017;Wang et al, 2017). Clinical studies have shown that testosterone concentration, sperm count and quality are declined, and the incidence of infertility is increased in aged men (Gunes et al, 2016;Almeida et al, 2017). In our study, we found icariin effectively ameliorated the age-related decline in testicular function by increasing testicular and epididymal weights and indices, sperm count and sperm viability, testicular testosterone concentrations, and seminiferous tubule diameters and heights.…”
Section: Discussionsupporting
confidence: 54%
“…sex hormones levels (Haji et al, 1994;Petersen et al, 2015;Li et al, 2017;Wang et al, 2017). Clinical studies have shown that testosterone concentration, sperm count and quality are declined, and the incidence of infertility is increased in aged men (Gunes et al, 2016;Almeida et al, 2017). In our study, we found icariin effectively ameliorated the age-related decline in testicular function by increasing testicular and epididymal weights and indices, sperm count and sperm viability, testicular testosterone concentrations, and seminiferous tubule diameters and heights.…”
Section: Discussionsupporting
confidence: 54%
“…61,62 As a confounding factor, ageing is linked to fertility issues, such as the decline in male hormones and sperm quality. 63 Therefore, an age threshold is required to investigate the effect of age on STL (such as < 30 years vs > 50 years, 0. 27,64 Herein, the age threshold has matched the age considered the start of the male fertility decline (35 years,.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this study has limitations, including the small number of cases from a 282 single-center, and the patients were older people, which may not represent the fecundity of 283 men in the golden age of childbearing. For example, the patients with COVID-19 were 284 examined in this study are all aging men and had comorbidities, which may compromise 285 spermatogenesis and male germ cell development (Almeida et al, 2017;Shiraishi and 286 Matsuyama, 2018). Nonetheless, our analysis suggests that this possibility is unlikely, 287 particularly since the degree of germ cell apoptosis in the patients with COVID-19 increased 288 significantly, whereas in the control patients (also aging men), it remained stable at a 289 significantly lower level.…”
Section: Results and Discussion 115mentioning
confidence: 99%